Knee Dislocations: Lessons Learned From 20-Year Follow-up - Schenck, Robert C. (Orthop J Sports Med, 2014)
BACKGROUND: Traumatic knee dislocation is becoming more prevalent because of improved recognition and increased exposure to high-energy trauma, but long-term results are lacking. PURPOSE: To present 2 cases with minimum 20-year follow-up and a review of the literature to illustrate some of the fundamental principles in the management of the dislocated knee. STUDY DESIGN: Review and case reports. METHODS: Two patients with knee dislocations who underwent multiligamentous knee reconstruction were reviewed, with a minimum 20-year follow-up. These patients were brought back for a clinical evaluation using both subjective and objective measures. Subjective measures include the following scales: Lysholm, Tegner activity, visual analog scale (VAS), Short Form–36 (SF-36), International Knee Documentation Committee (IKDC), and a psychosocial questionnaire. Objective measures included ligamentous examination, radiographic evaluation (including Telos stress radiographs), and physical therapy assessment of function and stability. RESULTS: The mean follow-up was 22 years. One patient had a vascular injury requiring repair prior to ligament reconstruction. The average assessment scores were as follows: SF-36 physical health, 52; SF-36 mental health, 59; Lysholm, 92; IKDC, 86.5; VAS involved, 10.5 mm; and VAS uninvolved, 2.5 mm. Both patients had excellent stability and were functioning at high levels of activity for their age (eg, hiking, skydiving). Both patients had radiographic signs of arthritis, which lowered 1 subject’s IKDC score to “C.” CONCLUSION: Knee dislocations have rare long-term excellent results, and most intermediate-term studies show fair to good functional results. By following fundamental principles in the management of a dislocated knee, patients can be given the opportunity to function at high levels. Hopefully, continued advances in the evaluation and treatment of knee dislocations will improve the long-term outcomes for these patients in the future.